International documents on environmental liability - Descamps, Hannes (Springer, 2008)
International Documents on Environmental Liability brings together 30 official full-text documents in the field of international environmental liability into an easily accessible, practical handbook; details the work of the International Law Commission on this topic; and provides the latest versions of international liability conventions and their statuses - including the latest on: 2003 UNECE Kyiv Liability Protocol 2004 EC Directive on Environmental Liability 2005 Antarctica Liability Annex The Authors' combined capacity as an academic, policy advisor, and practitioner have helped bring forth a publication that reflects their experience of being involved in the development, negotiations and implementation of environmental liability regimes at both an international and European level.